2022
DOI: 10.4236/ojs.2022.124030
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Communication Channels in Literary Texts

Abstract: The statistical theory of language translation is used to compare how a literary character speaks to different audiences by diversifying two important linguistic communication channels: the "sentences channel" and the "interpunctions channel". The theory can "measure" how the author shapes a character speaking to different audiences, by modulating deep-language parameters. To show its power, we have applied the theory to the literary corpus of Maria Valtorta, an Italian mystic of the XX-century. The likeness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(52 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…[12][13][14][15][16][17][18] report results not based on mathematical analyses of texts-as our theory does-and when a mathematical approach is used, as in Refs. , most of these studies consider neither Shannon's communication theory, nor the fundamental connection that some linguistic variables seem to have with reading ability and short-term memory (STM) capacity [1][2][3][4][5][6][7][8]. In fact, these studies are mainly concerned with automatic translations, not with a high-level direct response of human readers, as our theory is.…”
Section: A Mathematical Theory Of Texts Outside the Paradigm Of Natur...mentioning
confidence: 92%
See 2 more Smart Citations
“…[12][13][14][15][16][17][18] report results not based on mathematical analyses of texts-as our theory does-and when a mathematical approach is used, as in Refs. , most of these studies consider neither Shannon's communication theory, nor the fundamental connection that some linguistic variables seem to have with reading ability and short-term memory (STM) capacity [1][2][3][4][5][6][7][8]. In fact, these studies are mainly concerned with automatic translations, not with a high-level direct response of human readers, as our theory is.…”
Section: A Mathematical Theory Of Texts Outside the Paradigm Of Natur...mentioning
confidence: 92%
“…In recent papers [1][2][3][4][5][6][7][8], we have developed a general theory on the deep-language mathematical structure of literary texts (or any long text), including their translation. The theory is based on linguistic communication channels-suitably defined-always contained in texts and based on the theory of regression lines [9,10] and Shannon's communication and information theory [11].…”
Section: A Mathematical Theory Of Texts Outside the Paradigm Of Natur...mentioning
confidence: 99%
See 1 more Smart Citation
“…The history of Christianity has always been characterized by mystics, persons who claim having direct talks with Jesus and visions of his life, which they describe in literary works. In principle, any scientific assessment of the details contained in these writings would seem impossible but in some recent works (Matricciani & De Caro, 2017;Matricciani & De Caro, 2018;De Caro et al, 2020;De Caro et al, 2021b;Matricciani, 2022b) a series of scientific studies on the large literary Corpus written by Maria Valtorta, an Italian mystic of the XX century, have shown that many coherent data on Jesus' life and Palestine of 2000 years ago can be unexpectedly extracted and verified from her literary work. Her writings contain a large amount of historical, biblical, geographical, archaeological, astronomical and meteorological information, hardly attributable to her skills, not to mention her very poor health conditions, because Maria Valtorta received an education not sufficient to justify what emerges from her writings.…”
Section: A New Research Track Based On Mystical Visionsmentioning
confidence: 99%
“…By converting sequences of words into intervals, through a suitable reading/speaking speed, their duration was found to be realistic. Moreover, she can develop the literary character Jesus in such a way that he talks to specific audiences differently (Matricciani, 2022b). Maria Valtorta also describes apostle Peter's first burial site, which, she writes, was not on the Vatican Hill.…”
Section: A New Research Track Based On Mystical Visionsmentioning
confidence: 99%